Hubungan posisi dan lama duduk dengan nyeri punggung bawah pada pemain game online - Putu Gede Pradipta Mahardika Wijaya; Ida Ayu Sri Wijayanthi; Ketut Widyastuti (DiscoverSys Inc., 2019)
Introduction: The public's interest in online games is seen by the growing number of internet cafes and online games that are increasingly in Indonesia. Online games are starting to be considered something addictive. Position and duration of playing online game players that are usually more than 4 hours causes online game players often experience lower back pain. This study aims to determine the position and duration of sitting with low back pain in online game players.Methods: This study is a cross-sectional analytic study with a qualitative study design. The research data uses primary data taken directly by filling out the questionnaire in Game Online in the West Denpasar sub-district for the period November 2018 to December 2018. The sample collection technique uses the total sampling method.Result: The total sample in this study was 80 respondents, based on age distribution ranging from 17 to 30 years with an average age of 20.86 years. The highest proportion of body mass index in the risk group (> 23.0) was 55 people (68.75%). The proportion of ergonomic sitting positions is 20 people (25%) while the proportion of non-ergonomic sitting positions is 60 people (75%). The proportion of respondents who sat â‰¤4 hours was 23 people (28.75%) while the proportion of respondents sitting> 4 hours was 57 people (71.25%). The proportion of respondents who complained of low back pain was 60 people (75%) and those who did not complain of 20 lower back pain (25%). The highest proportion who experience low back pain in respondents with non-ergonomic sitting position is 75%. The highest proportion who experienced low back pain in respondents with a sitting time> 4 hour was 71.25%.Conclusion: Non-ergonomic sitting position and duration sitting that more than 4 hours are risk factors that affect lower back pain in online game players.Latar Belakang: Ketertarikan masyarakat terhadap game online tampak dengan berkembangnya usaha warung internet dan game-online yang semakin banyak di Indonesia. Aktivitas duduk dengan posisi dan durasi waktu bermain pemain game online yang biasanya lebih dari 4 jam menyebabkan para pemain game online sering mengalami nyeri punggung bawah. Penelitian ini bertujuan untuk mengetahui hubungan posisi dan lama duduk dengan nyeri punggung bawah pada pemain game online.Metode: Penelitian ini merupakan penelitian analitik cross-sectional dengan desain studi kualitatif. Data penelitian menggunakan data primer yang diambil langsung dengan pengisian kuisioner di Game Online wilayah kecamatan Denpasar Barat periode November 2018 hingga Desember 2018. Teknik pengumpulan sampel menggunakan metode total sampling.Hasil: Total sampel pada penelitian ini adalah 80 responden, berdasarkan distribusi usia berkisar 17 hingga 30 tahun dengan rerata usia 20,86 tahun. Proporsi indeks massa tubuh terbanyak pada kelompok berisiko (>23,0) sebanyak 55 orang (68,75%). Proporsi posisi duduk ergonomis sebanyak 20 orang (25%) sedangkan proporsi posisi duduk tidak ergonomis sebesar 60 orang (75%). Proporsi responden yang duduk 4jam sebesar 23 orang (28,75%) sedangkan proporsi responden yang duduk >4jam sebesar 57 orang (71,25%). Proporsi responden yang mengeluh nyeri punggung bawah ada 60 orang (75%) dan yang tidak mengeluh adanya nyeri punggung bawah sebanyak 20 orang (25%). Proporsi paling banyak yang mengalami nyeri punggung bawah pada responden dengan posisi duduk tidak ergonomis sebesar 75%. Proporsi paling banyak yang mengalami nyeri punggung bawah pada responden dengan lama duduk >4jam sebesar 71,25%.Simpulan: Posisi duduk tidak ergonomis dan lama duduk lebih dari 4 jam merupakan faktor risiko yang mempengaruhi nyeri punggung bawah pada pemain game online.